Flow Cytometric Determination of Circulating Progenitor Cells in Patients With Pulmonary Arterial Hypertension: A Systematic Review - Kimia Heydari; Carrie Johnson; I. Diane Cooper; Kadija Hersi; Carl Tanba; Junfeng Sun; Michael A. Solomon; Jason M. Elinoff (Pulmonary Circulation)
ABSTRACT Pulmonary arterial hypertension (PAH) is characterized by progressive narrowing and obliteration of distal, pre‐capillary pulmonary vessels. Yet, noninvasive biomarkers that reflect this disease‐defining process are lacking. A systematic review of PAH studies that measured circulating progenitor cells (CPCs) or circulating endothelial cells (CECs) in PAH by flow cytometry was performed to understand how future studies, leveraging state‐of‐the‐art single‐cell analyses, can advance the field. The study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews. Of the 2422 studies identified, 20 met inclusion criteria. Nineteen studies measured CPCs by flow cytometry, only one study examined CECs. A total of 647 PAH patients were included across all 19 CPC studies. Marker schemes chosen to define CPCs, and the methods of flow cytometry used, varied significantly across studies. Meta‐analysis of a subgroup of CPC studies (n = 8) similarly identified a significant amount of heterogeneity even amongst studies using the same marker scheme. In conclusion, a systematic review of CPC studies in PAH patients reveals the limitations of the current literature. Future studies should include contemporary risk assessments, disease duration, reporting of comorbid conditions, and serial sampling over time. Furthermore, methods that incorporate best practices for detecting rare cell populations by flow cytometry are essential and should be reported in sufficient detail in future publications. With the emergence of single‐cell technologies, future studies of circulating progenitor and endothelial cells in PAH remain relevant and may incorporate several insights from the current review to build upon the existing literature.